2018
DOI: 10.1111/tmi.13070
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes about cervical cancer and its prevention among female secondary school students in Nigeria

Abstract: Overall knowledge of cervical cancer is poor, but attitudes are positive. Awareness campaigns are therefore necessary, and are expected to be effective. Campaigns should target teenage females, and commencing teaching in high schools of developing countries, through materials included in their academic curricula, is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 15 publications
5
36
0
2
Order By: Relevance
“…This difference is likely to due to differences in the age of the participants. The lack of cervical cancer knowledge reported in our study is similar to a Tanzanian study (30.9%) [34] and lower than the results from a Nigerian study (42.7%) [4]. The Tanzanian data was based on a 2011-12 survey, whereas the Nigerian sample was of high school students from 13 to 25 years, surveyed in 2018.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This difference is likely to due to differences in the age of the participants. The lack of cervical cancer knowledge reported in our study is similar to a Tanzanian study (30.9%) [34] and lower than the results from a Nigerian study (42.7%) [4]. The Tanzanian data was based on a 2011-12 survey, whereas the Nigerian sample was of high school students from 13 to 25 years, surveyed in 2018.…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, it contributes to the largest cause of potential years of life lost due to young age onset in women between 35 and 50 years [2,3]. Both the higher incidence and mortality rates result from a lack of or low uptake in screening and preventative measures, late diagnosis, cost and availability of treatments and high human immunodeficiency virus (HIV) infection rates [4].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the questionnaires included both positively and negatively worded questions, only the positively worded ones were included in the analysis. This is because, related papers have revealed that the positively worded questions were representative of the participants' views.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce speculative responses, some questions in Parts 3 and 4 were worded negatively, while others were positive. However, only the positively-worded ones were analysed because an earlier but related paper [17] showed that these were representative of the participants' views.…”
Section: The Questionnaire: Design Despatch and Returnmentioning
confidence: 99%
“…[8][9][10] They also improve perceptions, [11,12] screening uptakes, [11,[13][14][15] and the adoption of positive behaviours among those affected. [16] A recent paper [17] suggested that health campaigns in developing countries should be targeted at young, senior secondary (high) school students, who are predominantly in their mid-to-late teens. Arguably, this suggestion is justified because, in a country like Nigeria, 15.6% of 16-year-old girls are already sexually exposed, [2] while 51.7% of university undergraduates become sexually active before they turn 20.…”
Section: Introductionmentioning
confidence: 99%